2020
DOI: 10.1186/s12889-020-09525-4
|View full text |Cite
|
Sign up to set email alerts
|

States with fewer criminalizing immigrant policies have smaller health care inequities between citizens and noncitizens

Abstract: Background In the last thirty years, major shifts in immigrant policy at national and state levels has heightened boundaries among citizens, permanent residents, and those with other statuses. While there is mounting evidence that citizenship influences immigrant health care inequities, there has been less focus on how policies that reinforce citizenship stratification may shape the extent of these inequities. We examine the extent to which the relationship between citizenship and health care i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 33 publications
2
19
0
1
Order By: Relevance
“…24 "Le-gality" or "illegality"-an expression of structural discrimination-is another social determinant of health that contributes to immigrants' vulnerability to poor health, injury, and violence. 14,25,26 Health risks associated with illegality, which extend to citizen children in mixed-status families, include psychosocial stressors (for example, fear of deportation), direct physical threats (for example, family separation), and diminished access to health-promoting resources such as health care. These stressors are associated with adverse child developmental and health outcomes.…”
Section: Immigrant Status As a Social Determinant Of Healthmentioning
confidence: 99%
“…24 "Le-gality" or "illegality"-an expression of structural discrimination-is another social determinant of health that contributes to immigrants' vulnerability to poor health, injury, and violence. 14,25,26 Health risks associated with illegality, which extend to citizen children in mixed-status families, include psychosocial stressors (for example, fear of deportation), direct physical threats (for example, family separation), and diminished access to health-promoting resources such as health care. These stressors are associated with adverse child developmental and health outcomes.…”
Section: Immigrant Status As a Social Determinant Of Healthmentioning
confidence: 99%
“…2 - 6 Protective laws and policies promote health and well-being among immigrants, their families, and communities by reducing stress levels, increasing access to health and other services, and addressing broader social drivers of health such as employment, housing, education, and transportation. 7 - 11 …”
Section: Introductionmentioning
confidence: 99%
“…Such connections are evident in many policy domains. For example, scholars who study immigration have identified critical linkages between politics, processes of racialization, and health (Kline 2019;LeBrón et al 2018;Lopez 2019;Pedraza 2018a, 2018b;Pedraza, Cruz Nichols, and LeBrón 2017;Novak, Geronimus, and Martinez-Cardoso 2017;Young, Beltrán-Sánchez, and Wallace 2020). Similarly, a small but burgeoning literature on Medicaid policy has amplified the tripartite significance of racism, health and politics in that arena (Franklin 2017;Grogan and Park 2017;Quadagno 2016, 2021;Leitner, Hehman, and Snowden 2018;Michener 2018Michener , 2020Michener , 2021Snowden and Graaf 2019).…”
mentioning
confidence: 99%
“…Even scholars who do such work are often not aware of one another (as reflected in citation practices and as a Forthcoming in Journal of Health Politics, Policy and Law. DOI: 10.1215/03616878-9517149 result of disciplinary boundaries) and are not robustly engaged by scholars in other related areas (e.g., scholars of health policy too easily overlook work related to racism and health policy) (for notable examples of scholarship that does address work on racism and health policy see Hooijer and King 2021;Grogan and Park 2017;Kline 2019;Lanford and Quadagno 2021;LeBrón et al 2018;LeBrón et al 2019;Lopez 2019; Michener 2018Michener , 2020 Pedraza 2018a, 2018b;Pedraza, Cruz Nichols, and LeBrón 2017;Novak, Geronimus, and Martinez- Cardoso 2017;Young, Beltrán-Sánchez, and Wallace 2020). Putting this array of literatures and approaches into conversation and engagement with one another is an important step in producing knowledge useful for advancing health equity.…”
mentioning
confidence: 99%